Analysis of the fine-mesh subgroup method and its feasible improvement - Li, Song; Zhang, Qian; Liu, Lei; Zhang, Yongfa; Hao, Jianli; Wang, Xiaolong; Jiang, Lizhi; Liu, Xiaoya (Frontiers in Energy Research, 2023)
The fine-mesh subgroup method (FSM) is proposed to treat the significant resonance self-shielding effect both effectively and accurately. Similar to the ultra-fine group method, the fine-mesh subgroup method adopts a fine group structure on the resonance energy range to avoid the extra resonance interference effect correction. To improve the efficiency, on the one hand, the one-group micro-level optimization is adopted, so the subgroup fixed-source equations will be only calculated on a certain number of pre-determined subgroup levels, and an interpolation process is employed to obtain the actual subgroup flux. On the other hand, the slowing-down calculation is carried out for group condensation for multigroup transport calculation. The main theory and feasible improvements of the fine-mesh subgroup method are analyzed in this paper. Several pin cell and lattice problems are applied to test the performance of the fine-mesh subgroup method, and the particle swarm optimization method is adopted to find the better group structure. The numerical results indicate a good performance both for accuracy and efficiency.